Viewing the (Re)Animated Irish Elk and Wolf: Identity Formation in Animated Films The Last Elk (1998) and Wolfwalkers (2020) - Sophie Quin (Estudios Irlandeses)
This paper considers how the Irish elk and wolf, two species long extinct within Ireland, are imbued with symbolic national and cultural significance in Cartoon Saloon’s feature film Wolfwalkers (Moore and Stewart 2020) and Brown Bag’s short The Last Elk (Shannon 1998). Lauri Honko’s concept of identity formation, built upon the key words “history”, “myth” and “symbol”, provides a methodological approach, allowing the viewer to explore how the wolf and Irish elk became symbolic of a naturalised “Irishness” within these animated fiction films. Analysis of character and environmental design decisions that directly define the physical form of the animated animal onscreen considers how these symbolically potent creatures are framed alongside motifs borrowed from Celtic art and iconography. Meanwhile, the use of sight and “gaze”, as discussed in Berger’s influential essay “Why Look at Animals?” (2022 [1977]), is essential to building a picture of the human and non-human connection within these narratives and poses questions surrounding the human-centric leanings these narratives take. Finally, the paper considers how the presence of extinction is a major theme that links the use of the animal in each film and potentially reflects late 20th and 21st century concerns for the environment borne out within 2d animation.